A116 LOSS OF RESPONSE TO VEDOLIZUMAB MAINTENANCE THERAPY IN CROHN`S DISEASE. (1st March 2018) - Ma, C; Kotze, P; Almutairdi, A; Al-Darmaki, A; Devlin, S; Kaplan, G G; Seow, C; Novak, K L; Lu, C; Ferraz, J; Stewart, M J; Buresi, M c; et al.
Abstract: Background: Vedolizumab is a gut-specific alpha-4-beta-7 integrin antagonist that has demonstrated efficacy in induction and maintenance of clinical response and remission in Crohn's disease randomized controlled trials. Aims: To evaluate the long-term maintenance of response achieved with vedolizumab therapy in Crohn's disease in the real-world setting. Methods: A retrospective cohort study was performed at the University of Calgary of adult (≥18 years) CD patients responding to vedolizumab within 6 months of standard induction therapy (vedolizumab 300mg IV at weeks 0, 2, and 6) followed by a scheduled maintenance vedolizumab IV regimen. The primary outcome was composite loss of response (LOR) in follow-up, defined by worsening symptoms requiring vedolizumab dose escalation, rescue medical therapy with corticosteroids or immunomodulators, or vedolizumab discontinuation. Survival analysis with Kaplan-Meier plots was performed to assess median time to LOR and probability of LOR in follow-up. Results: 109 CD patients with symptomatic response within 6 months to vedolizumab induction therapy were followed for a mean duration of 46.3 weeks (SD ±31.3 weeks). Mean Harvey Bradshaw Index (HBI) at induction was 6.3 (± 3.2); 68.8% (75/109) of patients had previously failed biologic therapy and 45 patients (41.3%) had previously failed multiple biologic agents. Composite loss of response occurred in 36 patients (33.0%) in follow-up at a mean time of 35.2 weeks (± 20.9 weeks). Dose escalation of vedolizumab to 300mg IV every four weeks was required in 22 patients (20.1%) to optimize primary clinical response in the context of ongoing symptoms despite every eight week therapy. Dose escalation for secondary loss of response occurred in 10 patients (9.2%) at a mean time of 38.9 weeks (± 5.0 weeks). Addition of rescue corticosteroids or immunomodulators was attempted in six patients (5.5%). Vedolizumab was discontinued due to loss of response in 22 patients (20.2%); mean time to drug discontinuation was 42.3 weeks (± 23.3 weeks). At 52 weeks, the probability of developing a composite loss of response was 36.7% [95% CI: 26.6 – 49.2%]. The probability of continuing on vedolizumab therapy at 52 weeks among initial symptomatic responders was 75.6% [95% CI: 62.8 – 84.5%]. Conclusions: Over three quarters of patients who respond symptomatically to vedolizumab induction therapy continue on treatment at one year, but 1/3 of patients will experience a loss of response and approximately 20% will discontinue treatment due to loss of response during maintenance therapy. Funding Agencies: None